Jamaica : Sixth Review Under the Arrangement Under the Extended Fund Facility. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
Discussions centered on the preparations for the 2015/16 budget, and reforms to strengthen the financial sector and boost growth. The authorities have deepened their efforts in supporting their ambitious fiscal goals by strengthening public financial management and revenue administration, and they reiterated their resolve to continue containing the wage bill. Steps have also been identified to advance the reform of the securities dealers and to increase the resilience of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet